ImproviApplication of ICT-Based Problem Based Learning Method as a Learning Innovation for Pancasila Education to Improve Learning Outcomes of Class VII D Students of SMPN 51 Palembangng Student Motivation in Learning Pancasila Education with Bamboozle Media Games in Class VII B SMP Negeri 51 Palembang - Rafindo, Yanuar; Dianti, Puspa; Linda Hartati, Laili (Jurnal Profesi Pendidikan, 2025)
This study aims to improve the effectiveness of learning outcomes of students in class VII D SMPN 51 Palembang in the subject of Pancasila Education, especially the material of Unity in Diversity, through the application of the Problem Based Learning (PBL) learning model by utilizing ICT media. The research method used is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were obtained through observation, interviews, and evaluation of learning outcomes using Google Form. The results showed that the application of ICT-based PBL was able to increase the active participation of students, improve the learning process, and improve learning outcomes significantly. Learning media such as interactive presentations through Canva and online evaluation based on Google Form make learning more interesting and accessible to students. Based on the evaluation results in cycle II, there was an increase in the class average score which showed the achievement of the success indicator. Thus, the ICT-based PBL model is effectively applied in learning Pancasila Education to encourage active learning, critical thinking, and deeper understanding.